A high first-efficiency negative electrode material for lithium-ion secondary battery and preparation method thereof
By using vapor deposition method to deposit metal lithium and nanosilicon particles in the negative electrode material of lithium-ion secondary batteries and forming carbon shells, the problems of material fracture caused by volume expansion and low Coulomb efficiency are solved, and efficient lithium supplementation and electrochemical performance improvements are achieved.
Patent Information
- Application Number
- CN202211633601.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-19
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2042-12-19
AI Technical Summary
The negative electrode material of lithium-ion secondary battery breaks the material due to volume expansion during charging and discharging, resulting in a decrease in electrochemical activity, low efficiency of Coulomb, and the lithium supplement method is cumbersome and has no obvious effect.
The metal lithium particles and nanosilicon particles are deposited at intervals in the through holes of the porous carbon microspheres by vapor deposition to form a uniformly distributed structure to avoid nanosilicon agglomeration and the formation of lithium dendrites, and at the same time, the carbon shell is formed by vapor deposition.
Effectively reduce the volume expansion effect, improve the first Coulomb efficiency of the negative electrode material, simplify the lithium supplement process, and improve the cycling performance and energy density of the battery.
Smart Images

Figure CN115732666B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a high first-efficiency negative electrode material for lithium-ion secondary batteries and a preparation method thereof. Background Art
[0002] Silicon has a theoretical specific capacity of 4200mAh / g. It can store more lithium ions than graphite negative electrodes, and the battery energy density is relatively high, which effectively improves the endurance and mileage. Because of its high theoretical capacity, low lithium insertion and extraction potential, environmental friendliness, and abundant reserves, it is regarded as the most promising next-generation lithium battery negative electrode material.
[0003] The alloying reaction of lithium ions and silicon causes a large volume expansion, which will generate a large amount of shear stress and compressive stress, causing the material particles to break and blocking the direct transmission of electrons on the material particles. As the number of charge and discharge cycles increases, the impact of volume expansion becomes more severe, causing the material particles to break seriously or even pulverize, which in turn causes some materials to completely lose their electrochemical activity, resulting in reduced battery capacity and poor cycle performance. At the same time, during the first charging process of a lithium-ion battery, a solid electrolyte interface (SEI) film will form on the surface of the negative electrode, consuming a portion of the lithium ions, forming irreversible capacity, and resulting in low coulombic efficiency.
[0004] Nano-sizing of silicon can solve the problem of volume expansion to a certain extent, but it is still difficult to evenly disperse it in carbon materials. The low coulombic efficiency caused by the consumption of lithium ions can be improved by replenishing lithium. The existing methods of replenishing lithium are generally replenishing lithium with lithium foil, lithium powder, electrochemical lithium and positive electrode, which are cumbersome and ineffective. Summary of the invention
[0005] The embodiment of the present invention provides a high first-efficiency negative electrode material for lithium-ion secondary batteries and a preparation method thereof. Metal lithium particles and nano-silicon particles are formed by depositing gas lithium and silicon-containing gas intervals in the through holes of porous carbon microspheres. On the one hand, the obtained nanoscale silicon particles have a grain size of less than 45nm, which effectively reduces the volume expansion effect. At the same time, nano-silicon and metal lithium are alternately deposited, which can form a uniform distribution in the porous carbon microspheres and avoid the agglomeration of nano-silicon. On the other hand, the co-deposition of metal lithium and silicon intervals into the porous carbon microspheres can fully exert the lithium replenishment effect while avoiding the formation of lithium dendrites due to uneven distribution of lithium, thereby improving the first coulomb efficiency of the negative electrode material.
[0006] The above-mentioned method for replenishing lithium in the negative electrode material provided by the embodiment of the present invention is simple and easy to operate, and can be applied to mass production, so that the metal lithium particles are evenly distributed in the nano-silicon particles to avoid the formation of lithium dendrites.
[0007] In a first aspect, an embodiment of the present invention provides a high first-efficiency negative electrode material for a lithium-ion secondary battery, the high first-efficiency negative electrode material comprising: a porous carbon matrix, metallic lithium particles, nano-silicon particles and a carbon shell;
[0008] Wherein, the porous carbon matrix is a porous carbon microsphere containing through holes; the average pore size of the through holes is 1nm-50nm;
[0009] The metal lithium particles are deposited in the through holes by gaseous lithium; the nano silicon particles are deposited in the through holes by silicon-containing gas;
[0010] The mass of the metal lithium particles accounts for 10%-50% of the total mass of the high first-efficiency negative electrode material;
[0011] The particle size of the nano silicon particles is between 0.1nm and 45nm, and the mass of the nano silicon particles accounts for 20% to 70% of the total mass of the high first-efficiency negative electrode material;
[0012] The high first-cycle coulombic efficiency of the high first-cycle negative electrode material used in lithium-ion secondary batteries is 99%-105%.
[0013] Preferably, the mass of the carbon shell accounts for 1%-20% of the total mass of the high first-efficiency negative electrode material;
[0014] The particle size of the high first-effect negative electrode material is between 1 μm and 100 μm.
[0015] In a second aspect, an embodiment of the present invention provides a method for preparing a high first-efficiency negative electrode material for a lithium-ion secondary battery as described in the first aspect above, wherein the preparation method is a vapor deposition method, specifically comprising:
[0016] Step S1, under an argon atmosphere, placing porous carbon microspheres containing through-holes in a deposition chamber of a deposition device, placing metallic lithium in a second furnace chamber of the deposition device to evaporate into gaseous lithium at high temperature, bringing the gaseous lithium from the second furnace chamber into the deposition chamber by a carrier gas, and allowing the gaseous lithium to be deposited in the pores of the through-holes of the porous carbon microspheres to form metallic lithium particles;
[0017] Step S2, introducing a silicon-containing gas into a deposition chamber to deposit the silicon-containing gas in the pores of the porous carbon microspheres to form nano silicon particles;
[0018] Step S3, alternately repeating step S1 and step S2, introducing gaseous lithium and silicon-containing gas at intervals, so that metallic lithium particles and nano-silicon particles are uniformly deposited in the through holes of the porous carbon microspheres, to obtain a precursor material;
[0019] Step S4, carbon-coating the above-mentioned precursor material by a gas phase method to form a dense carbon shell on the outer surface of the porous carbon microspheres to obtain a high first-efficiency negative electrode material.
[0020] Preferably, the deposition equipment includes any one of a vapor deposition furnace, a tube furnace, a rotary furnace, a bell furnace or a fluidized bed;
[0021] The deposition chamber is connected to the second furnace chamber via a first air inlet, and the parameters of the automatic air inlet valve of the first air inlet can be adjusted to control the deposition amount of the gaseous lithium;
[0022] The deposition chamber has a second gas inlet on the outside thereof, and the deposition amount of the silicon-containing gas is controlled by adjusting the parameters of the automatic gas inlet valve of the second gas inlet;
[0023] The temperature of evaporating into gaseous lithium at high temperature is 800° C.-1500° C., and the insulation time is 1 hour-20 hours;
[0024] The carrier gas is argon gas, and the flow rate is 1L / min-50L / min.
[0025] Preferably, the silicon-containing gas includes one or more silane gases selected from the group consisting of monosilane, disilane, trisilane, dichlorosilane, trichlorosilane and tetrachlorosilane.
[0026] Preferably, the deposition temperature of the silicon-containing gas is 600° C.-1500° C., the vapor deposition time is 1 hour-20 hours, and the gas flow rate is 0.5 L / min-50 L / min.
[0027] Preferably, the method of carbon coating the above-mentioned precursor material by the gas phase method is specifically as follows: depositing the carbon source gas at a temperature of 450°C-1000°C on the outer surface of the porous carbon microspheres in which the metal lithium particles and nano-silicon particles are uniformly deposited in the through holes to form a carbon shell;
[0028] Wherein, the carbon source gas includes: one or more of methane, ethane, propane, butane, acetylene and propylene; the flow rate of the carbon source gas is 1L / min-50L / min, and the deposition time is 1 hour-15 hours.
[0029] Preferably, in step 1 and step 2, industrial silicon powder and metallic lithium are used as raw materials by a thermal plasma method, and gaseous lithium and silicon vapor are deposited in the pores of the through-holes of the porous carbon microspheres in a thermal plasma treatment device to obtain the precursor material.
[0030] In a third aspect, an embodiment of the present invention provides a negative electrode plate, wherein the negative electrode plate includes the high first-efficiency negative electrode material described in the first aspect.
[0031] In a fourth aspect, an embodiment of the present invention provides a lithium-ion secondary battery, wherein the lithium battery comprises the negative electrode plate described in the third aspect.
[0032] The embodiment of the present invention provides a high first-efficiency negative electrode material for lithium-ion secondary batteries and a preparation method thereof. Metal lithium particles and nano-silicon particles are formed by depositing gas lithium and silicon-containing gas intervals in the through holes of porous carbon microspheres. On the one hand, the obtained nanoscale silicon particles have a grain size of less than 45nm, which effectively reduces the volume expansion effect. At the same time, nano-silicon and metal lithium are alternately deposited, which can form a uniform distribution in the porous carbon microspheres and avoid the agglomeration of nano-silicon. On the other hand, the co-deposition of metal lithium and silicon intervals into the porous carbon microspheres can fully exert the lithium replenishment effect while avoiding the formation of lithium dendrites due to uneven distribution of lithium, thereby improving the first coulomb efficiency of the negative electrode material.
[0033] The above-mentioned method for replenishing lithium in the negative electrode material provided by the embodiment of the present invention is simple and easy to operate, and can be applied to mass production, so that the metal lithium particles are evenly distributed in the nano-silicon particles to avoid the formation of lithium dendrites. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.
[0035] Figure 1 It is a flow chart of a method for preparing a high first-efficiency negative electrode material prepared by a chemical vapor deposition method provided in an embodiment of the present invention.
[0036] Figure 2 It is a schematic structural diagram of a cross section of a high first-efficiency negative electrode material provided in an embodiment of the present invention.
[0037] Figure 3 It is a charge and discharge curve diagram of a battery assembled with the high first-efficiency negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0038] The present invention is further described in detail below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.
[0039] An embodiment of the present invention provides a high first-efficiency negative electrode material for a lithium-ion secondary battery, the high first-efficiency negative electrode material comprising: a porous carbon matrix, metallic lithium particles, nano-silicon particles and a carbon shell; the particle size of the high first-efficiency negative electrode material is between 1 μm and 100 μm; the high first-efficiency negative electrode material has a first-cycle coulombic efficiency of 99% to 105% for a lithium-ion secondary battery.
[0040] The porous carbon matrix is a porous carbon microsphere containing through-holes; the average pore size of the through-holes is 1nm-50nm;
[0041] The metal lithium particles are deposited in the through-holes by gaseous lithium, and the particle size of the metal lithium particles is between 0.1nm and 45nm; the nano silicon particles are deposited in the through-holes by silicon-containing gas, and the particle size of the nano silicon particles is between 0.1nm and 45nm.
[0042] The mass of the metallic lithium particles accounts for 10%-50% of the total mass of the high first-efficiency negative electrode material, preferably 20-40%; the mass of the nano-silicon particles accounts for 20%-70% of the total mass of the high first-efficiency negative electrode material, preferably 40-65%; the mass of the carbon shell accounts for 1%-20% of the total mass of the high first-efficiency negative electrode material, preferably 15-20%.
[0043] The embodiment of the present invention provides a method for preparing the above-mentioned high first-efficiency negative electrode material, and the preparation method is a vapor deposition method, such as Figure 1 As shown, specifically including:
[0044] Step S1, under an argon atmosphere, placing porous carbon microspheres containing through-holes in a deposition chamber of a deposition device, placing metallic lithium in a second furnace chamber of the deposition device to evaporate into gaseous lithium at high temperature, bringing the gaseous lithium from the second furnace chamber into the deposition chamber by a carrier gas, and allowing the gaseous lithium to be deposited in the pores of the through-holes of the porous carbon microspheres to form metallic lithium particles;
[0045] Wherein, the deposition equipment includes any one of a vapor deposition furnace, a tubular furnace, a rotary furnace, a bell furnace or a fluidized bed;
[0046] The deposition chamber is connected to the second furnace chamber via a first air inlet, and the parameters of the automatic air inlet valve of the first air inlet can be adjusted to control the deposition amount of gaseous lithium;
[0047] The deposition chamber is provided with a second gas inlet on the outside, and the deposition amount of the silicon-containing gas is controlled by adjusting the parameters of the automatic gas inlet valve of the second gas inlet;
[0048] The temperature for evaporating into gaseous lithium at high temperature is 800°C-1500°C, and the holding time is 1 hour-20 hours;
[0049] The carrier gas is argon with a flow rate of 1L / min-50L / min.
[0050] Step S2, introducing a silicon-containing gas into a deposition chamber to deposit the silicon-containing gas in the pores of the porous carbon microspheres to form nano silicon particles;
[0051] The silicon-containing gas includes one or more silane gases selected from the group consisting of monosilane, disilane, trisilane, dichlorosilane, trichlorosilane and tetrachlorosilane.
[0052] The deposition temperature of the silicon-containing gas is 600° C.-1200° C., the vapor deposition time is 1 hour-20 hours, and the gas flow rate is 0.5 L / min-50 L / min.
[0053] Step S3, alternately repeating step S1 and step S2, introducing gaseous lithium and silicon-containing gas at intervals, so that metallic lithium particles and nano-silicon particles are uniformly deposited in the through holes of the porous carbon microspheres, to obtain a precursor material;
[0054] Wherein, within the deposition time range, the time interval between each introduction of gaseous lithium and silicon-containing gas is 0.5 hour to 1 hour.
[0055] Step S4, carbon-coating the above-mentioned precursor material by a gas phase method to form a dense carbon shell on the outer surface of the porous carbon microspheres to obtain a high first-efficiency negative electrode material;
[0056] The method of carbon coating the above-mentioned precursor material by the gas phase method is specifically as follows: the carbon source gas is deposited on the outer surface of the porous carbon microspheres in which the metal lithium particles and the nano-silicon particles are uniformly deposited in the through holes at a temperature of 450°C-1000°C to form a carbon shell; the carbon source gas includes one or more of methane, ethane, propane, butane, acetylene and propylene; the flow rate of the carbon source gas is 1L / min-50L / min, and the deposition time is 1 hour-15 hours.
[0057] In the present application, in step S2, the deposition temperature of the silicon-containing gas is 600°C-1500°C, preferably 600°C-1200°C, for example, it can be 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C or any temperature in the range. If the temperature is lower than 600°C, the silicon-containing gas material is not fully cracked. If the temperature is higher than 1200°C, the nano-silicon generated by the cracking and reduction of the silicon-containing gas material is severely crystallized, and the silicon grain size is larger, which affects the cycle performance of the material, and at high temperature, silicon reacts with carbon to generate silicon carbide, which affects the conductive properties of the material.
[0058] In the present application, in the above-mentioned preparation method, in step S3, step S1 and step S2 are repeated alternately, and the order can be not determined, and step S2 can be performed first and then S1. As long as the metal lithium particles and nano-silicon particles can be evenly deposited in the through holes of the porous carbon microspheres at intervals, the formation of lithium dendrites can be avoided while improving the coulomb efficiency of the first cycle.
[0059] In an optional scheme, steps 1 and 2 of the above preparation method can also be carried out by a thermal plasma method using industrial silicon powder and metallic lithium as raw materials. In a thermal plasma treatment device, gaseous lithium and silicon vapor are deposited in the pores of the through-holes of the porous carbon microspheres to obtain a precursor material.
[0060] The schematic diagram of the structure of the high first-efficiency negative electrode material for lithium-ion secondary batteries prepared by the above preparation method is as follows: Figure 2 As shown, it can be seen that metal lithium particles and nano-silicon particles are deposited in the through holes of the porous carbon microspheres.
[0061] The high first-efficiency negative electrode material provided in the embodiment of the present invention can be used as a negative electrode material active substance for a negative electrode material of a lithium battery, and can be used to prepare a negative electrode plate of a lithium-ion secondary battery. The negative electrode plate of the present application also includes a negative electrode current collector. The present application has no special restrictions on the negative electrode current collector, as long as it can achieve the purpose of the present application. For example, it can include but is not limited to copper foil, copper alloy foil, nickel foil, stainless steel foil, foam nickel, foam copper or composite current collector, etc.
[0062] The lithium ion secondary battery using the high first-cycle coulombic efficiency negative electrode material provided by the embodiment of the present invention as the negative electrode active material has a high first-cycle coulombic efficiency.
[0063] In order to better understand the technical solution provided by the present invention, the following uses multiple specific examples to illustrate the preparation process of the high first-efficiency negative electrode material for lithium-ion secondary batteries of the present invention, as well as the method and characteristics of applying it to lithium batteries.
[0064] Example 1
[0065] This embodiment provides a preparation process and performance test of a high first-efficiency negative electrode material for a lithium-ion secondary battery, and the specific steps are as follows.
[0066] Step S1, under argon atmosphere, placing porous carbon microspheres containing through holes in a deposition chamber of a deposition device, placing metallic lithium in a second furnace chamber of the deposition device to evaporate into gaseous lithium at a high temperature of 800°C, and bringing the gaseous lithium from the second furnace chamber into the deposition chamber through a carrier gas argon gas with a flow rate of 0.5L / min, so that the gaseous lithium is deposited in the pores of the through holes of the porous carbon microspheres to form metallic lithium particles, and the deposition time is 20 hours.
[0067] Step S2, introducing monosilane at a flow rate of 0.5 L / min into a deposition chamber at a temperature of 600° C., and depositing it in the pores of the through-holes of the porous carbon microspheres to form nano-silicon particles, and the deposition time is 20 hours.
[0068] Step S3, alternately repeating step S1 and step S2, respectively introducing gaseous lithium and silicon-containing gas at intervals of 0.5 hours, so that metallic lithium particles and nano-silicon particles are evenly deposited in the through holes of the porous carbon microspheres, to obtain a precursor material.
[0069] Step S4, carbon coating the above precursor material by gas phase method, using methane with a flow rate of 1L / min, and depositing at 450°C for 15 hours to form a dense carbon shell on the outer surface of the porous carbon microspheres to obtain a high first-efficiency negative electrode material.
[0070] The high first-efficiency negative electrode material prepared in this embodiment is used to prepare a negative electrode sheet assembly battery, and the test is performed as follows:
[0071] Preparation of negative electrode sheets: The obtained high first-effect negative electrode material, conductive additive carbon black, and adhesive (1:1 sodium carboxymethyl cellulose and styrene-butadiene rubber) are weighed according to a mass ratio of 95:2:3, and slurry is prepared in a beater at room temperature. The prepared slurry is evenly coated on the copper foil, dried in a forced air drying oven at 50°C for 2 hours, cut into 8×8mm sheets, and vacuum dried in a vacuum drying oven at 100°C for 10 hours. The dried sheets are then transferred to the glove box for standby use for battery assembly.
[0072] Assembled battery: The assembly of simulated battery was carried out in a glove box containing high-purity Ar atmosphere, using metallic lithium as the counter electrode and a solution of 1 mol of LiPF6 in ethylene carbonate (EC) / dimethyl carbonate (DMC) (volume ratio v:v=1:1) as the electrolyte to assemble the battery.
[0073] Test: Use a charge and discharge instrument to perform constant current charge and discharge mode test, the discharge cut-off voltage is 0.005V, the charge cut-off voltage is 1.5V, and the charge and discharge test is performed at a current density of C / 10. The charge and discharge curve is as follows: Figure 3 The test data is shown in Table 1.
[0074] Example 2
[0075] This embodiment provides a preparation process and performance test of a high first-efficiency negative electrode material for a lithium-ion secondary battery, and the specific steps are as follows.
[0076] Step S1, under argon atmosphere, placing porous carbon microspheres containing through holes in a deposition chamber of a deposition device, placing metallic lithium in a second furnace chamber of the deposition device to evaporate into gaseous lithium at a high temperature of 900°C, and bringing the gaseous lithium from the second furnace chamber into the deposition chamber through a carrier gas argon gas with a flow rate of 5L / min, so that the gaseous lithium is deposited in the pores of the through holes of the porous carbon microspheres to form metallic lithium particles, and the deposition time is 18 hours.
[0077] Step S2, introducing trisilane gas at a flow rate of 5 L / min into a deposition chamber at a temperature of 650° C., and depositing it in the pores of the through-holes of the porous carbon microspheres to form nano-silicon particles, and the deposition time is 18 hours.
[0078] Step S3, alternately repeating step S1 and step S2, respectively introducing gaseous lithium and silicon-containing gas at intervals of 1 hour, so that metallic lithium particles and nano-silicon particles are evenly deposited in the through holes of the porous carbon microspheres to obtain a precursor material.
[0079] Step S4, carbon coating the above precursor material by gas phase method, using ethane with a flow rate of 5L / min, depositing at 500°C for 14 hours, forming a dense carbon shell on the outer surface of the porous carbon microspheres, and obtaining a high first-efficiency negative electrode material.
[0080] The high first-efficiency negative electrode material prepared in this embodiment was used to prepare negative electrode plates and assemble batteries for testing. The specific process was the same as in Example 1. The test results are detailed in Table 1.
[0081] Example 3
[0082] This embodiment provides a preparation process and performance test of a high first-efficiency negative electrode material for a lithium-ion secondary battery, and the specific steps are as follows.
[0083] Step S1, under argon atmosphere, placing porous carbon microspheres containing through holes in a deposition chamber of a deposition device, placing metallic lithium in a second furnace chamber of the deposition device to evaporate into gaseous lithium at a high temperature of 1000°C, and bringing the gaseous lithium from the second furnace chamber into the deposition chamber by a carrier gas argon with a flow rate of 10L / min, so that the gaseous lithium is deposited in the pores of the through holes of the porous carbon microspheres to form metallic lithium particles, and the deposition time is 16 hours.
[0084] Step S2, introducing dichlorosilane at a flow rate of 10 L / min into a deposition chamber at a temperature of 700° C., and depositing it in the pores of the through-holes of the porous carbon microspheres to form nano-silicon particles, and the deposition time is 16 hours.
[0085] Step S3, alternately repeating step S1 and step S2, respectively introducing gaseous lithium and silicon-containing gas at intervals of 0.5 hours, so that metallic lithium particles and nano-silicon particles are evenly deposited in the through holes of the porous carbon microspheres, to obtain a precursor material.
[0086] Step S4, carbon coating the above precursor material by gas phase method, using propane with a flow rate of 10L / min, depositing at 550°C for 12 hours, forming a dense carbon shell on the outer surface of the porous carbon microspheres, and obtaining a high first-efficiency negative electrode material.
[0087] The high first-efficiency negative electrode material prepared in this embodiment was used to prepare negative electrode plates and assemble batteries for testing. The specific process was the same as in Example 1. The test results are detailed in Table 1.
[0088] Example 4
[0089] This embodiment provides a preparation process and performance test of a high first-efficiency negative electrode material for a lithium-ion secondary battery, and the specific steps are as follows.
[0090] Step S1, under argon atmosphere, placing porous carbon microspheres containing through holes in a deposition chamber of a deposition device, placing metallic lithium in a second furnace chamber of the deposition device to evaporate into gaseous lithium at a high temperature of 1100°C, and bringing the gaseous lithium from the second furnace chamber into the deposition chamber through a carrier gas argon gas with a flow rate of 15L / min, so that the gaseous lithium is deposited in the pores of the through holes of the porous carbon microspheres to form metallic lithium particles, and the deposition time is 14 hours.
[0091] Step S2, introducing trichlorosilane gas at a flow rate of 15 L / min into a deposition chamber at a temperature of 750° C., and depositing it in the pores of the through-holes of the porous carbon microspheres to form nano-silicon particles, and the deposition time is 14 hours.
[0092] Step S3, alternately repeating step S1 and step S2, respectively introducing gaseous lithium and silicon-containing gas at intervals of 1 hour, so that metallic lithium particles and nano-silicon particles are evenly deposited in the through holes of the porous carbon microspheres to obtain a precursor material.
[0093] Step S4, carbon coating the above precursor material by gas phase method, using butane with a flow rate of 15L / min, depositing at 600°C for 10 hours, forming a dense carbon shell on the outer surface of the porous carbon microspheres, and obtaining a high first-efficiency negative electrode material.
[0094] The high first-efficiency negative electrode material prepared in this embodiment was used to prepare negative electrode plates and assemble batteries for testing. The specific process was the same as in Example 1. The test results are detailed in Table 1.
[0095] Example 5
[0096] This embodiment provides a preparation process and performance test of a high first-efficiency negative electrode material for a lithium-ion secondary battery, and the specific steps are as follows.
[0097] Step S1, under argon atmosphere, placing porous carbon microspheres containing through holes in a deposition chamber of a deposition device, placing metallic lithium in a second furnace chamber of the deposition device to evaporate into gaseous lithium at a high temperature of 1200°C, and bringing the gaseous lithium from the second furnace chamber into the deposition chamber through a carrier gas argon gas with a flow rate of 20L / min, so that the gaseous lithium is deposited in the pores of the through holes of the porous carbon microspheres to form metallic lithium particles, and the deposition time is 12 hours.
[0098] Step S2, introducing monosilane at a flow rate of 20 L / min into a deposition chamber at a temperature of 800° C., and depositing it in the pores of the through-holes of the porous carbon microspheres to form nano-silicon particles, and the deposition time is 12 hours.
[0099] Step S3, alternately repeating step S1 and step S2, respectively introducing gaseous lithium and silicon-containing gas at intervals of 1 hour, so that metallic lithium particles and nano-silicon particles are evenly deposited in the through holes of the porous carbon microspheres to obtain a precursor material.
[0100] Step S4, carbon coating the above precursor material by gas phase method, using acetylene with a flow rate of 20L / min, and depositing at 650°C for 15 hours to form a dense carbon shell on the outer surface of the porous carbon microspheres to obtain a high first-efficiency negative electrode material.
[0101] The high first-efficiency negative electrode material prepared in this embodiment was used to prepare negative electrode plates and assemble batteries for testing. The specific process was the same as in Example 1. The test results are detailed in Table 1.
[0102] Example 6
[0103] This embodiment provides a preparation process and performance test of a high first-efficiency negative electrode material for a lithium-ion secondary battery, and the specific steps are as follows.
[0104] Step S1, under argon atmosphere, placing porous carbon microspheres containing through holes in a deposition chamber of a deposition device, placing metallic lithium in a second furnace chamber of the deposition device to evaporate into gaseous lithium at a high temperature of 1300°C, and bringing the gaseous lithium from the second furnace chamber into the deposition chamber through a carrier gas argon gas with a flow rate of 25L / min, so that the gaseous lithium is deposited in the pores of the through holes of the porous carbon microspheres to form metallic lithium particles, and the deposition time is 10 hours.
[0105] Step S2, introducing monosilane at a flow rate of 25 L / min into a deposition chamber at a temperature of 900° C., and depositing it in the pores of the through-holes of the porous carbon microspheres to form nano-silicon particles, and the deposition time is 10 hours.
[0106] Step S3, alternately repeating step S1 and step S2, respectively introducing gaseous lithium and silicon-containing gas at intervals of 0.5 hours, so that metallic lithium particles and nano-silicon particles are evenly deposited in the through holes of the porous carbon microspheres, to obtain a precursor material.
[0107] Step S4, carbon coating the above precursor material by gas phase method, using propylene with a flow rate of 25L / min, depositing at 700°C for 6 hours, forming a dense carbon shell on the outer surface of the porous carbon microspheres, and obtaining a high first-efficiency negative electrode material.
[0108] The high first-efficiency negative electrode material prepared in this embodiment was used to prepare negative electrode plates and assemble batteries for testing. The specific process was the same as in Example 1. The test results are detailed in Table 1.
[0109] Example 7
[0110] This embodiment provides a preparation process and performance test of a high first-efficiency negative electrode material for a lithium-ion secondary battery, and the specific steps are as follows.
[0111] Step S1, under argon atmosphere, placing porous carbon microspheres containing through holes in a deposition chamber of a deposition device, placing metallic lithium in a second furnace chamber of the deposition device to evaporate into gaseous lithium at a high temperature of 1400°C, and bringing the gaseous lithium from the second furnace chamber into the deposition chamber through a carrier gas argon with a flow rate of 30L / min, so that the gaseous lithium is deposited in the pores of the through holes of the porous carbon microspheres to form metallic lithium particles, and the deposition time is 5 hours.
[0112] Step S2, introducing monosilane at a flow rate of 30 L / min into a deposition chamber at a temperature of 1000° C., and depositing it in the pores of the through-holes of the porous carbon microspheres to form nano-silicon particles, and the deposition time is 5 hours.
[0113] Step S3, alternately repeating step S1 and step S2, respectively introducing gaseous lithium and silicon-containing gas at intervals of 1 hour, so that metallic lithium particles and nano-silicon particles are evenly deposited in the through holes of the porous carbon microspheres to obtain a precursor material.
[0114] Step S4, carbon-coating the above-mentioned precursor material by a gas phase method, using a mixed gas of methane and ethane (volume ratio of 1:1) with a flow rate of 15L / min, depositing at 800°C for 4 hours, forming a dense carbon shell on the outer surface of the porous carbon microspheres, and obtaining a high first-efficiency negative electrode material.
[0115] The high first-efficiency negative electrode material prepared in this embodiment was used to prepare negative electrode plates and assemble batteries for testing. The specific process was the same as in Example 1. The test results are detailed in Table 1.
[0116] Example 8
[0117] This embodiment provides a preparation process and performance test of a high first-efficiency negative electrode material for a lithium-ion secondary battery, and the specific steps are as follows.
[0118] Step S1, under argon atmosphere, placing porous carbon microspheres containing through holes in a deposition chamber of a deposition device, placing metallic lithium in a second furnace chamber of the deposition device to evaporate into gaseous lithium at a high temperature of 1450°C, and bringing the gaseous lithium from the second furnace chamber into the deposition chamber through a carrier gas argon gas with a flow rate of 40L / min, so that the gaseous lithium is deposited in the pores of the through holes of the porous carbon microspheres to form metallic lithium particles, and the deposition time is 3 hours.
[0119] Step S2, introducing monosilane at a flow rate of 40 L / min into a deposition chamber at a temperature of 1100° C., and depositing it in the pores of the through-holes of the porous carbon microspheres to form nano-silicon particles, and the deposition time is 3 hours.
[0120] Step S3, alternately repeating step S1 and step S2, respectively introducing gaseous lithium and silicon-containing gas at intervals of 1 hour, so that metallic lithium particles and nano-silicon particles are evenly deposited in the through holes of the porous carbon microspheres to obtain a precursor material.
[0121] Step S4, carbon coating the above precursor material by gas phase method, using methane with a flow rate of 20L / min, depositing at 900°C for 2 hours, forming a dense carbon shell on the outer surface of the porous carbon microspheres, and obtaining a high first-efficiency negative electrode material.
[0122] The high first-efficiency negative electrode material prepared in this embodiment was used to prepare negative electrode plates and assemble batteries for testing. The specific process was the same as in Example 1. The test results are detailed in Table 1.
[0123] Example 9
[0124] This embodiment provides a preparation process and performance test of a high first-efficiency negative electrode material for a lithium-ion secondary battery, and the specific steps are as follows.
[0125] Step S1, under argon atmosphere, placing porous carbon microspheres containing through holes in a deposition chamber of a deposition device, placing metallic lithium in a second furnace chamber of the deposition device to evaporate into gaseous lithium at a high temperature of 1500°C, and bringing the gaseous lithium from the second furnace chamber into the deposition chamber through a carrier gas argon gas with a flow rate of 50L / min, so that the gaseous lithium is deposited in the pores of the through holes of the porous carbon microspheres to form metallic lithium particles, and the deposition time is 1 hour.
[0126] Step S2, introducing monosilane at a flow rate of 50 L / min into a deposition chamber at a temperature of 1200° C., and depositing it in the pores of the through-holes of the porous carbon microspheres to form nano-silicon particles, and the deposition time is 1 hour.
[0127] Step S3, alternately repeating step S1 and step S2, respectively introducing gaseous lithium and silicon-containing gas at intervals of 0.5 hours, so that metallic lithium particles and nano-silicon particles are evenly deposited in the through holes of the porous carbon microspheres, to obtain a precursor material.
[0128] Step S4, carbon coating the above precursor material by gas phase method, using methane with a flow rate of 12.5L / min, depositing at 1000°C for 1 hour, forming a dense carbon shell on the outer surface of the porous carbon microspheres, and obtaining a high first-efficiency negative electrode material.
[0129] The high first-efficiency negative electrode material prepared in this embodiment was used to prepare negative electrode plates and assemble batteries for testing. The specific process was the same as in Example 1. The test results are detailed in Table 1.
[0130] Example 10
[0131] This embodiment provides a preparation process and performance test of a high first-efficiency negative electrode material for a lithium-ion secondary battery, using a thermal plasma method, and the specific process is as follows:
[0132] 400g of industrial silicon powder is used as a silicon source, and 300g of metal lithium sheets is used as a lithium source. The industrial silicon powder and the lithium sheets are placed in a high temperature zone of a plasma treatment device respectively. 1kg of porous carbon microspheres with through holes are placed in a condensation zone of the plasma treatment device. In an argon atmosphere, the industrial silicon powder and the metal lithium sheets are gasified and decomposed into silicon-containing gas and gaseous lithium respectively by the plasma treatment device. The silicon-containing gas and gaseous lithium are brought into the condensation zone alternately 10 times by carrier gas argon, so that metal lithium particles and nano-silicon particles are uniformly deposited in the through holes of the porous carbon microspheres to obtain a precursor material. Then, a carbon source methane with a flow rate of 12L / min is introduced, and deposition is performed at 1000°C for 1 hour. The precursor material is carbon-coated to obtain a high first-efficiency negative electrode material.
[0133] The high first-efficiency negative electrode material prepared in this embodiment was used to prepare negative electrode plates and assemble batteries for testing. The specific process was the same as in Example 1. The test results are detailed in Table 1.
[0134] In order to better illustrate the effects of the embodiments of the present invention, a comparative example is compared with the embodiment.
[0135] Comparative Example 1
[0136] This comparative example provides a conventional silicon-carbon composite material preparation method and performance test, and the specific steps include:
[0137] Step S1: 200 g of nano silicon particles and 500 g of phenolic resin powder are added to a hydrothermal kettle for hydrothermal reaction at a pressure of 5 MPa, a heating temperature of 300° C. and a holding time of 8 hours. The material is washed and filtered until the filtrate is transparent and colorless, and then dried to obtain a spherical precursor material.
[0138] Step S2: placing the spherical precursor material into a reaction device, heating it to 900° C. at a heating rate of 3° C. / min, and carbonizing it for 6 hours in a nitrogen atmosphere to obtain a conventional silicon-carbon composite material.
[0139] The conventional silicon-carbon composite material prepared in this comparative example was used to prepare the negative electrode plate and assemble the battery for testing. The specific process was the same as that in Example 1. The test results are detailed in Table 1.
[0140] Comparative Example 2
[0141] This comparative example provides a preparation process and performance test of a silicon-carbon composite material. Different from Example 1, this comparative example only deposits nano-silicon particles in the through-holes of the porous carbon microspheres, and does not deposit metal lithium particles. The specific steps are as follows.
[0142] 1) Under argon atmosphere, monosilane is brought into the deposition chamber of a vapor deposition furnace by a carrier gas argon with a flow rate of 0.5 L / min for vapor deposition, and the deposition is carried out at 800° C. for 20 hours, so that the silicon-containing gas is deposited into the pores of the through-holes of the porous carbon microspheres to form nano-silicon particles, thereby obtaining a precursor material.
[0143] 2) The precursor material is vapor-coated to form a carbon shell to obtain a silicon-carbon composite material.
[0144] The silicon-carbon composite material prepared in this comparative example was used to prepare a negative electrode sheet and assembled into a button cell for testing. The specific process was the same as in Example 1. The test results are detailed in Table 1.
[0145] Comparative Example 3
[0146] This comparative example provides a preparation process and performance test of a negative electrode material. Different from Example 1, this comparative example is a negative electrode material obtained by alternately depositing nano-silicon particles and metallic lithium particles in the pores of porous carbon microspheres without through holes and then performing gas-phase carbon coating.
[0147] The negative electrode material prepared in this comparative example was used to prepare a negative electrode sheet and assembled into a button cell for testing. The specific process was the same as that in Example 1. The test results are detailed in Table 1.
[0148] Table 1 shows the test results of the charge specific capacity and the first-cycle coulomb efficiency of the batteries assembled in Examples 1-10 and Comparative Examples 1-3.
[0149] Serial number Charge specific capacity (mAh / g) First week efficiency (%) Example 1 1739 103.43 Example 2 1725 102.42 Example 3 1720 100.44 Example 4 1725 99.85 Example 5 1729 102.87 Example 6 1737 100.17 Example 7 1738 101.26 Example 8 1751 103.74 Example 9 1746 102.86 Example 10 1740 102.1 Comparative Example 1 1212 78.92 Comparative Example 2 1898 92.34 Comparative Example 3 1356 99.81
[0150] By comparing the test data in Table 1, it can be seen that the batteries assembled with the high first-efficiency negative electrode materials provided in Examples 1-10 of the present invention have super high first-cycle efficiency relative to Comparative Examples 1-2, and have higher charging specific capacity relative to Comparative Examples 1 and 3. This is because the high first-efficiency negative electrode materials prepared in Examples 1-10 of the present invention are formed by depositing gas lithium and silicon-containing gas intervals in the through holes of porous carbon microspheres to form metal lithium particles and nano-silicon particles. On the one hand, the obtained nanoscale silicon particles have a grain size of less than 45nm, which effectively reduces the volume expansion effect. At the same time, nano-silicon and metal lithium are alternately deposited, which can form a uniform distribution in the porous carbon microspheres, avoiding the agglomeration of nano-silicon. On the other hand, the co-deposition of metal lithium and silicon intervals into the porous carbon microspheres can fully exert the lithium replenishment effect while avoiding the formation of lithium dendrites due to uneven distribution of lithium, thereby improving the first coulombic efficiency of the negative electrode material.
[0151] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A high first-efficiency negative electrode material for lithium-ion secondary batteries, characterized in that: The high first-effect negative electrode material comprises: a porous carbon matrix, metal lithium particles, nano silicon particles and a carbon shell; Wherein, the porous carbon matrix is a porous carbon microsphere containing through holes; the average pore size of the through holes is 1nm-50nm; The metal lithium particles are deposited in the through-holes by gaseous lithium; the nano silicon particles are deposited in the through-holes by silicon-containing gas; the metal lithium and the nano silicon particles are formed by depositing the gaseous lithium and the silicon-containing gas in the through-holes of the porous carbon microspheres at intervals; The mass of the metal lithium particles accounts for 10%-50% of the total mass of the high first-efficiency negative electrode material; The particle size of the nano silicon particles is between 0.1nm and 45nm, and the mass of the nano silicon particles accounts for 20% to 70% of the total mass of the high first-efficiency negative electrode material; The high first-cycle coulombic efficiency of the high first-cycle negative electrode material used in lithium-ion secondary batteries is 99%-105%.
2. The high first-efficiency negative electrode material for lithium-ion secondary batteries according to claim 1, characterized in that: The mass of the carbon shell accounts for 1%-20% of the total mass of the high first-efficiency negative electrode material; The particle size of the high first-effect negative electrode material is between 1 μm and 100 μm.
3. A method for preparing a high first-efficiency negative electrode material for a lithium-ion secondary battery according to any one of claims 1 to 2, characterized in that: The preparation method is a vapor deposition method, which specifically comprises: Step S1, under an argon atmosphere, placing porous carbon microspheres containing through-holes in a deposition chamber of a deposition device, placing metallic lithium in a second furnace chamber of the deposition device to evaporate into gaseous lithium at high temperature, bringing the gaseous lithium from the second furnace chamber into the deposition chamber by a carrier gas, and allowing the gaseous lithium to be deposited in the pores of the through-holes of the porous carbon microspheres to form metallic lithium particles; Step S2, introducing a silicon-containing gas into a deposition chamber to deposit the silicon-containing gas in the pores of the porous carbon microspheres to form nano silicon particles; Step S3, alternately repeating step S1 and step S2, introducing gaseous lithium and silicon-containing gas at intervals, so that metallic lithium particles and nano-silicon particles are uniformly deposited in the through holes of the porous carbon microspheres, to obtain a precursor material; Step S4, carbon-coating the above-mentioned precursor material by a gas phase method to form a dense carbon shell on the outer surface of the porous carbon microspheres to obtain a high first-efficiency negative electrode material.
4. The preparation method according to claim 3, characterized in that: The deposition equipment includes any one of a vapor deposition furnace, a tubular furnace, a rotary furnace, a bell furnace or a fluidized bed; The deposition chamber is connected to the second furnace chamber via a first air inlet, and the parameters of the automatic air inlet valve of the first air inlet can be adjusted to control the deposition amount of the gaseous lithium; The deposition chamber has a second gas inlet on the outside thereof, and the deposition amount of the silicon-containing gas is controlled by adjusting the parameters of the automatic gas inlet valve of the second gas inlet; The temperature of evaporating into gaseous lithium at high temperature is 800° C.-1500° C., and the insulation time is 1 hour-20 hours; The carrier gas is argon gas, and the flow rate is 1L / min-50L / min.
5. The preparation method according to claim 3, characterized in that: The silicon-containing gas includes one or more silane gases selected from the group consisting of monosilane, disilane, trisilane, dichlorosilane, trichlorosilane, and tetrachlorosilane.
6. The preparation method according to claim 3, characterized in that: The deposition temperature of the silicon-containing gas is 600° C.-1500° C., the vapor deposition time is 1 hour-20 hours, and the gas flow rate is 0.5 L / min-50 L / min.
7. The preparation method according to claim 3, characterized in that: The method of carbon coating the above-mentioned precursor material by the gas phase method is specifically as follows: depositing the carbon source gas at a temperature of 450° C. to 1000° C. on the outer surface of the porous carbon microspheres in which the metal lithium particles and nano-silicon particles are uniformly deposited in the through holes to form a carbon shell; Wherein, the carbon source gas includes: one or more of methane, ethane, propane, butane, acetylene and propylene; the flow rate of the carbon source gas is 1L / min-50L / min, and the deposition time is 1 hour-15 hours.
8. The preparation method according to claim 3, characterized in that: In step 1 and step 2, industrial silicon powder and metallic lithium are used as raw materials by a thermal plasma method. In a thermal plasma treatment device, gaseous lithium and silicon vapor are deposited in the pores of the through-holes of the porous carbon microspheres to obtain the precursor material.
9. A negative electrode plate, characterized in that: The negative electrode plate comprises the high first-efficiency negative electrode material described in any one of claims 1-2 above.
10. A lithium ion secondary battery, characterized in that: The lithium battery comprises the negative electrode sheet as described in claim 9 above.
Citation Information
Patent Citations
Silicon-carbon composite material with nano micropores and preparation method as well as application thereof
CN103311523A
Lithium metal composite material and modified material thereof, and preparation methods and applications of lithium metal composite material and modified material
CN114944470A
Nano silicon-carbon composite material for secondary lithium battery as well as preparation method and application of nano silicon-carbon composite material
CN115020689A
Cited By
High-initial-efficiency negative electrode material for lithium-ion secondary battery and preparation method therefor
EP4641662A1